al-Khaṭīb al-Baghdādī, Philotimo and the lifelong learning of hadīth and maʿnā - Jamil, Khairil Husaini (2017)
al-Ḥāfiẓ al-Khaṭib al-Baghdādī (463AH / 1071 CE) is a traditional historian, jurist, belletrist, and ḥadīth theorist who was well-known for his vast experience in the field of traditional transmission of ḥadīth. The testimony of Ibn Nuqṭah al-Ḥanbalī and al-Ḥāfiẓ Ibn Ḥajar al-ʿAsqalānī concerning his authority in the field is frequented repeatedly in many writings pertaining to the sciences of ḥadīth criticism. His encounter with various attitudes and approaches inside and outside the circle of traditional learners and scholars impinges upon his writings and many types of compositions he presented to the traditionists, tradents and traditionalists of Baghdād, Damascus and other towns in which he used to reside. This included his dedicated advice embedded in his famous work, Sharaf Aṣḥāb al-Ḥadīth (The Honour of the Fellows of Ḥadīth). Building on the concept of sharaf (honour) exploited in many of his writings, an attempt will be made to study the appearance of the Greek concept of philotimo in the context that surrounded the scholarship of al-Khaṭīb and the use of the concept in promoting the prevalent principle of lifelong learning in the Muslim community. The aim is to draw attention to the subtle ethos of expertness and longevity in ḥadīth scholarship and the accommodation of foreign concept in the pursuit of this endeavour. This will include a brief review of the concept of maʿnā employed in the context of this study and the ideal integration of ḥadīth and fiqh as a resultant notion of this scholastic labour.